Penerapan Prosedur Operasional Standar Make Up Room oleh Roomboy di Hotel Daima Padang - Pratiwi, Mega; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2016)
This study aims to determine the application of standard operating procedures make up room by roomboy at Daima Hotel Padang. This study consisted of 7 indicators of procedures, namely: tap the entrance to the room, open the window curtains, striping, making beds, cleaning the bath room, dusting and rechecking. This research is a descriptive study with qualitative data. The population in this study consists of 3 people. The collection of observation data to guide the interview. The results showed that the application of standard operating procedures make up room in Hotel Daima Padang has made 100% from 3 roomboy have done well and correctly. While based on each indicator: in particular indicator window curtains open, striping, making beds, dusting and rechecking already applied by all roomboy. While the knock on the door before entering the room and cleaning the bath room only 66.66% roomboy that implement them properly. Keywords: Make Up Room